2020 IEEE Congress on Evolutionary Computation (CEC) 2020
DOI: 10.1109/cec48606.2020.9185668
|View full text |Cite
|
Sign up to set email alerts
|

Improving Classification of Metamorphic Malware by Augmenting Training Data with a Diverse Set of Evolved Mutant Samples

Abstract: Detecting metamorphic malware provides a challenge to machine-learning models as trained models might not generalise to future mutant variants of the malware. To address this, we explore whether machine-learning models can be improved by augmenting training data-sets with samples of potential variants. These variants are generated using an evolutionary algorithm that evolves a behaviourally diverse set of mutants, optimised to avoid detection by a large set of existing detection-engines. Using features calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The various detection approaches depend on the kind of information employed when carrying out the analysis. Several other detection techniques have been suggested that involve the use of ML methods e.g Decision Trees (DT) in [10], Hidden Markov Models (HMM) in [37], Support Vector Machines (SVM) in [36] as well as a hybrid of both feature based and sequential ML models in [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The various detection approaches depend on the kind of information employed when carrying out the analysis. Several other detection techniques have been suggested that involve the use of ML methods e.g Decision Trees (DT) in [10], Hidden Markov Models (HMM) in [37], Support Vector Machines (SVM) in [36] as well as a hybrid of both feature based and sequential ML models in [9].…”
Section: Introductionmentioning
confidence: 99%
“…In [7] and [8], two EAs were used to generate training data which are used for the generation of the evolved malware mutants used in this work. These methods led to improved metamorphic malware detection within the context of feature based and sequential classifier [9]. The problem of limited training data was however noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation